Dampak Penggunaan Fungisida Sintetik pada Kelimpahan Cendawan Endofit Tanaman Padi - Rika Estria Gurusinga; Lilik Retnowati; Suryo Wiyono; Efi Toding Tondok (Jurnal Ilmu Pertanian Indonesia, 2020)
Application of fungicides to control rice diseases potentially have adverse effect on non target organisms including endophytic fungi. Unfortunately, information of fungicide effect on endophytic fungi on rice is still limited. The purpose of this research was to study the diversity and abundance of endophytic fungi on rice plant because of application of synthetic fungicides. There were two treatments in this study: non systemic fungicide (mankozeb) and systemic fungicide (difenoconazole) which were compared to control (without fungicide). Isolation of endophytic fungi and application of fungicides were conducted every week started at aged of 3 to 10 weeks after planting. Variables observed were total segment of rice colonized by endophytic fungi, colonization frequency of endophytic fungi, continued by identification and analysis of the diversity of endophytic fungi. This study showed that there was an increase in colonization of endophytic fungi with an increase of plant ages. The diversity of endophytic fungi was higher in stems than in leaves with the value of H' is 0.00-1.35 and 0.00-0.98 respectively. The most common types of endophytic fungi appear in each isolation of rice segments were Acremonium, Curvularia, Fusarium, Helminthosporium, Nigrospora, Penicillium, and Mucor. Both fungicides do not significantly affect the percentage of colonization and diversity of endophytic fungi. At the beginning of planting (4-6 MST) there was a decrease in the percentage of endophytic fungal colonization in the stem. From the percentage of colonization of each genus of fungi, Nigrospora and Fusarium decreased significantly with difenoconazole on the stem during the vegetative phase. Keywords: colonization, community, difenoconazole, diversity, mancozeb